An interconversion of oxazoline‐amido‐phenolate aluminium complexes: Structural, catalytic activity and density functional theory studies. (24th April 2021) - Chen, Ming‐Tsz; Chen, Yu‐Yang; Huang, Ting‐Hsun; Pi, Hui‐Chu; Hu, Ching‐Han; Chen, Chi‐Tien
Abstract : This paper describes a new mutual transformation mode occurred between two aluminium complexes, L 1 (AlMe2 )2 ·AlMe3 and (L 1 AlMe)2, which were generated upon different solvents and bearing the oxazoline‐amido‐phenolate ligand. Density functional theory (DFT) studies support plausible mechanisms. Their catalytic studies were investigated towards ring opening polymerization of ε‐caprolactone and l ‐lactide with the benzyl alcohol as the initiating reagent. Abstract : Two different types of aluminium complexes, L 1 (AlMe2 )2 ·AlMe3 and (L 1 AlMe)2 bearing the oxazolineamido‐phenolate ligand were generated upon different solvent synthetic routes. A new round transformation mode between these aluminium complexes as well as the DFT study supported a plausible mechanism. Their catalytic activities towards the ring opening polymerization of ε‐caprolactone and l ‐lactide in the presence of benzyl alcohol were investigated.